PENGEMBANGAN BUKU AJAR KAPITA SELEKTA MATEMATIKA DASAR BERBASIS TERPADU UNTUK MENINGKATKAN PEMECAHAN MASALAH MATEMATIS MAHASISWA - Diki Mulyana; Farid Gunadi (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
The purpose of this research was to develop valid tools for mathematic lessons. In this research, the developed lesson was basic mathematic capita selecta textbook based on Telaah, Eksplorasi, Rumuskan, Presentasikan, Aplikasikan, Duniawi dan Ukhrowi (TERPADU) to increase student’s problem solving in mathematic. The lesson tools which would be developed were: (1) Syllabus, (2) Semester Development Plan (SDP), (3) Textbook, and (4) Mathematic Problem Solving Skill Test, for students of Mathematic Educational Department, Wiralodra University. The development model used were lesson tools’s developing using Plomp modificate-model. The validity of lesson tools were assested by expert team validation and colleges. The result gained validation for tools developed by five experts and gained overall average score “usable”. This validation counted as an excellent category thus the tools are valid.